2019
DOI: 10.3390/ijerph16071266
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Sense of Coherence, and Coping with Stress as Predictors of Psychological Well-Being in the Course of Schizophrenia. The Study Design

Abstract: The main research objective was seeking for the predictive role of such personal resources as resilience, sense of coherence, and coping with stress in psychological well-being of schizophrenia patients and their treatment. The study group comprised 201 individuals with schizophrenia, aged between 18 and 62. The following instruments were used: The sense of coherence scale SOC-29, The resilience scale for adults, polish adaptation of the stress appraisal measure, semistructured clinical interview, the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 37 publications
(59 reference statements)
9
34
1
Order By: Relevance
“…However, in schizophrenia patients with cognitive impairment, there was no significant relationship observed between subjective happiness and level of functioning. This result is consistent with Izydorczyk and colleagues [ 14 ], who found an association between psychological well-being and cognitive disorganization.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, in schizophrenia patients with cognitive impairment, there was no significant relationship observed between subjective happiness and level of functioning. This result is consistent with Izydorczyk and colleagues [ 14 ], who found an association between psychological well-being and cognitive disorganization.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Palmer et al [ 4 ] found lower levels of happiness in patients diagnosed with schizophrenia compared to healthy controls, while Agid et al [ 11 ] observed no difference in the level of happiness between these two groups. Another methodological concern is that previous work investigating happiness and related factors in patients with schizophrenia did not include a control group [ 12 , 14 ]. The lack of consensus as to what constitutes happiness as a construct is another source of concern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scores for resilience and autonomy, and the total score were negatively correlated with the severity of negative symptoms. These results were in accordance with previous studies [57][58][59][60][61][62]. Although it had a two-factor structure, unlike the original version [52], we suggest that the index (total score) is valid for use with Cambodian patients with schizophrenia to evaluate their overall degree of QoL.…”
Section: Discussionsupporting
confidence: 91%